Does Amnioumbilicocerebral Ratio Better Predict Adverse Neonatal Outcomes in Comparison to Other Doppler Parameters in Late-Onset Fetal Growth Restriction? - Derya Kanza Gul; Nihal Callioglu (IMR Press, 2023)
Background: Pregnant women with late-onset fetal growth restriction (LFGR) are at high risk of perinatal morbidity and mortality. However, it is difficult to identify patients with a higher risk of adverse perinatal outcomes at the time of diagnosing FGR. The aim of this study is whether amniotic-umbilical-to-cerebral ratio (AUCR) is a better predictor than cerebroplacental ratio (CPR) and umblicocerebral ratio (UCR) in detecting short and long-term adverse perinatal outcomes (APO) in late-onset fetal growth restriction. Methods: Retrospective cohort study, Doppler examinations were performed between 35-37 weeks on pregnant women who were followed up in the obstetrics and gynecology outpatient clinic of Nisa Hospital between April 1st, 2012, and April 1st, 2022, and were considered to have delayed growth according to the Delphi consensus criteria. Sensitivity and specificity of measurements of UCR, CPR, and AUCR for predicting a negative intrapartum or postpartum outcome (fetal distress, Apgar score <7 at 5 minutes, umbilical arterial pH <7.1, admission of the newborn to the neonatal intensive care unit, intrauterine death) were evaluated. Receiver operating characteristic (ROC) curves and area under the ROC curve (AUC) were compared for UCR, CPR, and AUCR. Results: In this study, 185 pregnant women were evaluated. It was determined that 56 women had negative intrapartum or postpartum outcomes. UCR values were statistically significantly higher in the group with APO (p < 0.001), and the CPR (p < 0.001) and AUCR (p = 0.001) values were significantly lower in this group. The AUC values for CPR, UCR, and AUCR were 0.70 [95% confidence interval (CI): 0.62-0.79], 0.70 (95% CI: 0.62-0.79), and 0.66 (95% CI: 0.58-0.75), respectively. In the multivariate Logistic regression analysis of UCR, CPR, and AUCR values, there was no statistically significant correlation between CPR, UCR, and AUCR Doppler parameters in fetuses with LFGR in terms of detecting APO (p > 0.05). Conclusions: A low AUCR and CPR, and a high UCR were significantly associated with APO in fetuses with LFGR. There was no difference in the diagnostic performance between AUCR, CPR, and UCR in predicting adverse outcomes.